1993
DOI: 10.1007/bf00229648
|View full text |Cite
|
Sign up to set email alerts
|

Local cerebral glucose utilisation following acute and chronic bilateral carotid artery ligation in Wistar rats: relation to changes in local cerebral blood flow

Abstract: The effects on local cerebral blood flow (LCBF) and glucose utilisation (LCGU) of permanent, bilateral carotid artery ligation (BCAL) were studied in conscious Wistar rats. LCBF and LCGU were measured using quantitative autoradiographic 14C-iodoantipyrine and the 14C-2-deoxyglucose (14C-DG) techniques in 24 anatomically discrete regions of the brain. LCBF in the cerebral hemispheres 2.5 h (acute) after BCAL significantly decreased to 25-87% of the sham control, with the exception of the mammillary body. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Chronic cerebral hypoperfusion can be induced by permanent, bilateral occlusion of common carotid arteries (BCCAO) in rats, resulting in significant white matter lesions, learning and memory impairment, and hippocampal neuronal damage (Tsuchiya et al, 1993;Sarti et al, 2002). Thus, BCCAO in rats provides a model useful for understanding the pathophysiology of chronic cerebrovascular hypoperfusion and for screening drugs with potential therapeutic value for VaD (Wakita et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic cerebral hypoperfusion can be induced by permanent, bilateral occlusion of common carotid arteries (BCCAO) in rats, resulting in significant white matter lesions, learning and memory impairment, and hippocampal neuronal damage (Tsuchiya et al, 1993;Sarti et al, 2002). Thus, BCCAO in rats provides a model useful for understanding the pathophysiology of chronic cerebrovascular hypoperfusion and for screening drugs with potential therapeutic value for VaD (Wakita et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As well, the decrease in cerebral blood flow relates to the cognitive impairment seen in AD (Kasparova et al, 2005). Bilateral permanent occlusion of the common carotid arteries (BCCAO) in rats results in a significant reduction in cerebral blood flow; therefore, it is a useful model of chronic cerebral hypoperfusion (Tsuchiya et al, 1993). This animal model exhibits learning and memory impairments resembling those found in AD and VaD, accompanied by neuronal degeneration and microvascular abnormalities (Farkas et al, 2004).…”
mentioning
confidence: 99%
“…1 week of BCCAO (Tsuchiya et al, 1993). These regions include the cortex and hippocampus, which among other regions play important roles in learning and memory (Tsuchiya et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Permanent or transient bilateral occlusion of common carotid arteries in the rat is a model for whole brain ischemia and the local cerebral blood flow in anatomically discrete regions reportedly decreases to 25-8707o of the sham control at 2.5 hr after permanent occlusion of com mon carotid arteries (2VO) (3). We previously showed that 2VO caused impairment of spatial acquisition in a conventional 8-arm radial maze task and that this impair ment became more marked 1 to 4 months after the 2VO operation (4,5).…”
mentioning
confidence: 99%